Remote Working: Implications for Competitiveness and Productivity - Patrick Condon; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2021)
The COVID-19 pandemic has rapidly accelerated a shift to increased remote working. Remote working can deliver benefits to Irish enterprises, but can also have net cost implications. With remote working becoming more prevalent and affecting work patterns across the globe, all of Ireland's regions must remain competitive in order to continue to retain and attract FDI and skilled labour. Remote working can improve or hamper productivity, so it is important to implement the right policies to minimize the negative effects and maximize the positive effects of the adjustment to new work practices
Keywords: 330